PENGGAMBARAN DUNIA DALAM NOVEL PERJALANAN 99 CAHAYA DI LANGIT EROPA - Anis Mashlihatin (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
This paper discussed about the objective and the subjective observations which are used by the writer in representing the world when the writer is traveling. World is not just merely a landscape or places, but there is also people. Through objectivity point of view, the writer is taking distance with the world which is described. On the contrary, subjective observation emphasizes the personal involvement of the writer towards the described world. In this research, we can see in both places and people, subjective observation is more dominant than the objective observation. Observation always sets off from the objective point of view to the subjective point of view. Some places are described objectively, but then it shifted into subjective. Explicit subjective observation is more dominant than the implicit one. However, even if the quantity is lesser, the implicit subjectivity gives more significant influence.Keywords: objective, subjective, travel